Chronic myeloid leukemia treatment with Imatinib: An experience from a private tertiary care hospital - D C Doval; Ullas Batra; Sumit Goyal; Ajay Sharma; Saud Azam; Rashmi Shirali (Indian Journal of Medical and Paediatric Oncology)
The data presents 75 chronic myeloid leukemia patients diagnosed over a period 6 years i.e. from 2002 to 2008. The most common presentation was splenomegaly and 97% achieved complete hematological response at median duration of 4.3 weeks. The uniqueness of this study is follow-up with molecular response monitoring. Nearly, 30% patients achieved major molecular response (MMoR) by 12 months. 70% of patients achieved MMoR by median time of 60 months. Only 10% of the patient who achieved MMoR by 18 months had lost their responses subsequently.